2008
DOI: 10.1080/13697130801946779
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women's quality of life in the later half of life

Abstract: When developing programs to enhance health in post middle-age women, consideration should be given to symptom relief as well as quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…In this regard, Fallahzadeh (17), Sheikhan et al (29), and Ehsanpour et al (31) all reported a significant relationship between the sexual dimension of postmenopausal women's QoL and age and education. Research shows that educated women who are in better economic circumstances enjoy a higher QoL during menopause (14,15,32). Overall, the results of this study are consistent with the findings of the majority of similar studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Fallahzadeh (17), Sheikhan et al (29), and Ehsanpour et al (31) all reported a significant relationship between the sexual dimension of postmenopausal women's QoL and age and education. Research shows that educated women who are in better economic circumstances enjoy a higher QoL during menopause (14,15,32). Overall, the results of this study are consistent with the findings of the majority of similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, another aim of the present study was to compare the QoL of postmenopausal Iranian women with evidence from other countries. In this regard, studies have indicated that the prevalence of menopausal symptoms is markedly higher in Asian populations than in non-Asian populations, and the effects of these symptoms may have been underestimated (13,14). Although women throughout the world experience similar hormonal changes as a result of menopause, their menopausal experiences might be affected by sociodemographic characteristics, individual and cultural factors, and environmental conditions (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menopause affects the quality of life through alterations in hormones, moods, health, and overall physical condition (Chiu, Moore, Hsu, Huang, & Chuang, 2008). One may say that the quality of life consists of subjective and objective indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause can lower the quality of life through changes in hormone production, moods, health and physical conditions [2].…”
Section: Introductionmentioning
confidence: 99%